Fullerene‐based processable polymers as plausible acceptors in photovoltaic applications. Issue 4 (1st November 2012) - Perrin, Lara; Nourdine, Ali; Planes, Emilie; Carrot, Christian; Alberola, Nicole; Flandin, Lionel
Abstract To develop n‐type processable polymeric materials for photovoltaic applications, a series of polymers was synthesized by grafting fullerene C60 onto polystyrene (PS). Grafted polymers were studied and compared with PS:fullerene blends. Electronical and electrical properties were first measured to define the minimal amount of C60 required for solar cells application. Then, thermal properties and rheological behavior of grafted polymers were analyzed to determine whether they could be processed from the melt. A throughout experimental study revealed that C60‐grafted polymers exhibit two thresholds. The first threshold at 3–4 vol % (detected by electrical conductivity, electron mobility, and melt viscosity measurements) is associated to the percolation of C60 molecules. The second threshold (evidenced by glass transition and melt viscosity measurements and confirmed by optical and atomic force micrograph observations) at about 12–13 vol % is assumed to be related to the formation of C60 aggregates. © 2012 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2013